High chlamydia infection and its associated factors among patients seeking clinic-based STI services in Southern China: A preliminary cross-sectional study - Wang, Honglin; Weng, Rongxing; Zhang, Chunlai; Ye, Jianbin; Wen, Lizhang; Li, Jing; Lu, Yongyi; Ning, Ning; Hong, Fuchang; Chen, Xiangsheng; Cai, Yumao (Frontiers in Public Health, 2022)
Objective Chlamydia trachomatis (CT) infection is one of the most common sexually transmitted infections (STIs) worldwide. This study aimed to provide prevalence and associated factors data among patients seeking clinic-based STI services for estimating the disease burden of CT. Study design and method A cross-sectional survey was conducted among patients attending clinics for STI services. Patients' social-demographic and behavioral information was collected and CT infection was determined by nucleic acid amplification test (NAAT) with self-collected urine specimens. Associated factors were identified using logistic regression. Results Among the 8,324 participants, the overall prevalence was 9.0% with 10.7% for males and 8.3% for females respectively. Multivariate analysis showed that aged < 24 [adjusted odds ratio (aOR) = 1.27, 95% confidence interval (CI) = 1.01–1.59], being unmarried (aOR = 1.64, 95%CI = 1.35–2.00), having junior high school or below education level (aOR = 1.47, 95%CI = 1.13–1.91), having no access to health insurance (aOR = 1.27, 95%CI = 1.07–1.51), and being positive for Neisseria gonorrhoeae (NG, aOR = 4.49, 95%CI = 3.25–6.21) were significantly associated with CT infection. Conclusion We found that CT infection is prevalent among patients seeking clinic-based STI services in Southern China. Targeted interventions could be implemented for patients with a higher risk of CT infection including those aged < 24, being unmarried, having junior high school or below education level, having no access to health insurance, and being positive for NG. In addition, routine CT screening could be considered a public health strategy by the government.